PROSPEK INDUSTRI PENGOLAHAN PISANG GORENG DI KOTA MANADO - Juliando A. Supit; Theodora M. Katiandagho; Hanny Anapu; Ribka M. Kumaat (COCOS, 2013)
ABSTRACTThe objective of this research is to analyze the industry prospect of processing fried banana in Manado City by taking samples in the research region : Klabat Stadium and Malalayang Beach. Forty respondents were interviewed as representatives to the amount of consumer in Manado.This research was carried out at Klabat Stadium and Malalayang Beach from each location, two sellers were taken as samples start from September to October 2012. This research used primary and secondary data. Primary data were through directly interviewed with the owner and the employees of the sampel location and the forty respondents as the population of fried banana lovers. Secondary data taken through the literatures and institutions related with this reacerch. Analyzes data was showed in tables form.This research result showed that industry of processing fried banana in Manado City has a good prospect because it gained profit. Revenue Cost Ratio that obtained from each location is bigger than others. In condition like this business of fried banana deserves is feasible. Besides the profit sellers would obtain the opportunity doing this business is high because there are many consumers of this product in Manado City. Through this research we can see that there 234 sellers have the opportunity to start open business of fried banana.